Coffee Yield and Mineral Cycle in Intercropping of Coffea canephora and Some Species of Timber Shade Trees - Adi Prawoto (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2008)
Cocoa (Theobroma cacao L.) like most tropical trees is recalcitrant in tissue culture. Somatic embryogenesis is generally efficient micropropagation technique to multiply elite material. However, Somatic embryogenesis in cocoa is difficult and this species is considered as recalcitrant. One of the factors often considered as a component of in vitro recalsitrance is a high phenolic content and oxidation of these compounds. In cocoa tissue culture accumulate large amounts of poliphenolics compounds which probably impair further development. This study was conducted to investigate the composition of phenolic compounds in cocoa flower and leaves, and their changes troughout the somatic embryogenesis process. Calli were induced in cacao floral and leaves explants on a half-strenght Murashige and Skoog medium containing 30 g/L Glucose and combination of 2,4 dichlorophenoxyacetic acid (2,4 D) with kinetin (kin). Total polyphenol content was observed on Sulawesi 1 cocoa clone. Embryogenic and non-embryogenic callus were also compared. The percentage of callus production from flower tissue is 85%, percentage of embryogenic callus 40 %, although  the percentage of somatic embryo production from embryogenic callus callus is 70%. The conservation of callus into somatic embryos followed by decline in phenol content and an increase in peroxidase. The synthesis kinetics for these compounds in calli, under different somatic embryogenesis conditions, revealed a higher concentration under non-embryogenic conditions. So that, phenolic compound can influence the production of calli and an absence the phenolic compound can enhance production of somatic embryo.Kata kunci: Theobroma cacao L., polifenol, embrio somatik, kalus, flavonoid, katekin, in vitro recalcitance